Critical View of Safety: A Pathway for Safe Execution of Laparoscopic Cholecystectomy - Syed Hayder Alam, Danish Abdus Samad Chishti, Mirza Masoom Raza, Lubna Habib, Rahab Saeed, Fawad Talat (Pakistan Journal of Medical & Health Sciences, 2023)
The best method for treating gall bladder lithiasis is laparoscopic cholecystectomy. This original study objective was to assess the safety pathway’s critical viewpoint from a standpoint of laparoscopic cholecystectomy implementation safety. Material: Data was collected from patients who underwent laparoscopic cholecystectomy in the surgical divisions of Karachi. To gather information on the preoperative evaluation, surgical maintenance, and postoperative care of patients, as well as to determine whether the elements were isolated following the CVS after the process, a questionnaire was forwarded to the Digestive Pathologist Community. Records about icons were acquired and eventually examined by an auditor. Results: Information from 300 patients was analyzed. The selection of participants was separated into 2 groups based on the proof (A; n = 5) or lack (B; n = 295) of bile duct injury and intraoperative hemorrhage. The non-use of CVS was detected in 56.6% of operations in group A, and 26.8% in group B, and analyzing the operator-related factors the implementation of CVS was linked with a considerably reduced occurrence of bile duct injury and perioperative hemorrhage. Conclusion: The CVS has been proven that it is the safest method for identifying the Calot triangle’s components, and when used appropriately, it has a considerable effect on reducing intraoperative problems. To prevent extreme circumstances that might necessitate extra treatments, it would be beneficial to offer more instructional sessions on how to correctly apply CVS in medical care. Keywords: Cholecystectomy, laparoscopic, bile duct injury, surgery, bleeding, safety, gallbladder